Creative Methods in Learning Karo Dance as Teachers' Competence Improvements - Iskandar Muda; Yusnizar Heniwaty; Tuty Rahayu (Budapest International Research and Critics University, 2021)
Studying traditional dance is not only studying the movements, there are many things that must be known, understood, and understood to be able to dance. Landek (dance in the discussion of Batak Karo) as a local content of dance in North Sumatra, has now undergone many changes for various reasons. In addition to its development which is no longer based on its traditions, so that the existing creativity is not as expected. This is due to a lack of knowledge, understanding of the contextual context of dance in the learning process, so that students are no longer familiar with the traditional arts. For this reason, in an effort to re-familiarize the arts, learning with creative methods through textual and contextual approaches is an option in learning local dance (ethnic dance).